The 70th Anniversary of the Creation of the United Nations: Giving Peace a Chance - Christian Guillermet-Fernández; David Fernández Puyana (Cadmus, 2015)
War and peace perpetually alternate. Peace is always seen as an endless project, even a dream, to be realised in brotherhood by everyone all over the earth. During the last centuries, outstanding endeavours have been undertaken by the international community to create an international order free from wars through the strengthening of mechanisms aimed at promoting peaceful settlement of disputes. The UN Charter is the most solemn pact of peace in history, which lays down the necessary basic principles for an enduring peace, such as the full respect of fundamental rights. Today, in the context of the 70th Anniversary of the creation of the United Nations, the Human Rights Council should raise the voice of victims to strongly condemn war and to openly reiterate our inalienable right to live in a context in which war and conflict are progressively eliminated on earth through the promotion of mutual understanding, tolerance, respect for human rights and peaceful relationships.